Rusydi Ahmad Thuáimah: Maharah al-Qiraáh wa Ta'limuha - In'ami, Moh; Akbar, Ali; Zubairi, Ahmadun (Universitas Muhammadiyah Sumatera Barat, 2022)
Reading skill is not enough with the student's intelligence. Rather, he is concerned with the presence of external and internal factors that encourage reading. Reading is the main source for learning the Arabic language and requires special and varied training. The teacher should pay attention to the steps of teaching reading skill according to the intended purposes. The results of the research are: a). Reading skill is a complex process that includes four operations; It is recognition, understanding, criticism and interaction. Despite the clarity of the difference between these four processes, the exact definition of the language skills that pertain to each process is still a mystery to some teachers of Arabic as a second language; b). In reading, a process is intended to link the language of speech and written symbols. It is from this nature that the elements of reading are known, which are the mental meaning, the pronunciation to be performed, and the written symbol; c). The opinion of Rushdi Ahmed Tuaima in teaching reading skills The reading skill is taught when the stages of education are progressing so that teachers of reading skill in the Arabic language must be masters, absorbing the theoretical and practical aspects of reading education stages according to Rushdi Ahmed Tuaima, in succession and succession from the first stages to the last.